Analisis Penyerapan Energi Crash Box Pola Origami pada Pengujian Frontal Impact Posisi Angular Frontal - Bintarto, Redi; Atmaja, Andik; Kusyairi, Imam (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2017)
In the car, the body structure is designed in such a way so as to transfer and absorb energy. This serves to minimize the result of this accident related to kinetic energy. This needs a system to absorb the kinetic energy maximally, so as a result of a frontal collision events that can be reduced optimally and kinetic energy can be absorbed by a front body structure. Devices used for absorbing kinetic energy in the car is usually called a crash box, which is located between the main structure and bumper. Crash Box generally tubular thin shaped. It has been a lot of research about the crash box. In this study using crash box origami patterns and using methods taguchi orthogonal array L9 (34). AA7003-T7 aluminum material modeled as bilinear isotropic hardening, the loading method is Frontal Impact Frontal Angular Position with impact angles of 5, 15 and 30 degree by using the finite element software simulation methods. The simulation results showed that the crash box in the lowest possible energy absorption were happened at crash box with 5 degree, with 683 153 Joule energy absorbsion. The highest result was happened to crash box number 5 with the results of 3,140.778 Joule. Lowest absorption on impact of 15 degree and 30 degree were happened to crash box number 1 and number 3 with a value of 245 685 Joule and 174 845 Joule, while the highest absorption at mumber 3 with each value 1,708.521 Joule and 1,750.872 Joule.